PEREMPUAN ISLAMI DALAM NOVEL LOVE SPARKS IN KOREA KARYA ASMA NADIA KAJIAN SEMIOTIKA - Naimah , Naimah (Jurnal Sastra Aksara, 2018)
Knowing Islamic women in Love Sparks in Korea novel by Asma Nadia, the purpose of this study was to (1) to describe the image of Islamic women in the Love Sparks in Korea novel by Asma Nadia. (2) to describe the tendency of the author’s view of Islamic women in the Love Sparks in Korea novel by Asma Nadia. Using descriptive-qualitative method, this research was conducted by analyzing the text of Love Sparks in Korea novel by Asma Nadia. The source of the data in this study was taken from Love Sparks in Korea novel by Asma Nadia. Data collection technique was carried out by using the documentation method. The results of this study was the image of Islamic women in Love Sparks in Korea novel by Asma Nadia Semiotics Study. Researcher found out about the image of Islamic women from the physical, psychological, and social aspects. Physical image of Islamic women was portrayed as women who wear hijab, wear good dress, wear sneakers, and wear backpacks. The psychic image of Islamic women was portrayed from discipline, and strong. Whereas in the social image of Islamic women was portrayed as women who are polite, beneficial to parents, and has intelligence. The result of the tendency of the author’s view of Islamic women in the Love Sparks in Korea novel by Asma Nadia, the author tends to put Islamic women in the novel as Islamic women who want to reach the stage of perfection.